2007
DOI: 10.1016/j.molcel.2007.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Active and Repressive Chromatin Are Interspersed without Spreading in an Imprinted Gene Cluster in the Mammalian Genome

Abstract: The Igf2r imprinted cluster is an epigenetic silencing model in which expression of a ncRNA silences multiple genes in cis. Here, we map a 250 kb region in mouse embryonic fibroblast cells to show that histone modifications associated with expressed and silent genes are mutually exclusive and localized to discrete regions. Expressed genes were modified at promoter regions by H3K4me3 + H3K4me2 + H3K9Ac and on putative regulatory elements flanking active promoters by H3K4me2 + H3K9Ac. Silent genes showed two typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
143
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(164 citation statements)
references
References 33 publications
21
143
0
Order By: Relevance
“…The focal heterochromatin may be able to recruit transcriptional repressor complexes, such as CoREST and H3K4me3 demethylase, to regulate nucleosome occupancy in the active gene loci to repress expression of the cell growth genes. 37,38 This assertion was mainly supported by earlier studies showing that Rb-mediated repression of E2F target genes, including cyclin E, cyclin A2, cyclin D1 and B-Myb, was dependent on the formation of focal heterochromatin induced by SUV39 h1-mediated H3K9me3 and HP1 association. [39][40][41][42] Thus, any measures that impede H3K9me3 will change the overall nucleosome dynamics and destabilize the genome, leading to de-differentiation of the cells, aberrant gene expression and tumorigenic transformation.…”
Section: Discussionmentioning
confidence: 79%
“…The focal heterochromatin may be able to recruit transcriptional repressor complexes, such as CoREST and H3K4me3 demethylase, to regulate nucleosome occupancy in the active gene loci to repress expression of the cell growth genes. 37,38 This assertion was mainly supported by earlier studies showing that Rb-mediated repression of E2F target genes, including cyclin E, cyclin A2, cyclin D1 and B-Myb, was dependent on the formation of focal heterochromatin induced by SUV39 h1-mediated H3K9me3 and HP1 association. [39][40][41][42] Thus, any measures that impede H3K9me3 will change the overall nucleosome dynamics and destabilize the genome, leading to de-differentiation of the cells, aberrant gene expression and tumorigenic transformation.…”
Section: Discussionmentioning
confidence: 79%
“…H4K20, the only established Suv4-20h1 substrate, is typically not tri-methylated in transcriptionally active domains, and our preliminary studies did not reveal appreciable levels of H4K20-Me3 at glucocorticoid-inducible loci (data not shown). Recent findings, however, indicate that short heterochromatic regions enriched for H4K20-Me3 can be found within actively transcribed genes (24,28). Alternatively, Suv4-20h1 could modify nonhistone factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, having used fully differentiated lymphoblast cell lines in these experiments it remains possible that spreading might have occurred earlier and receded by the time of assay. It should be noted that the spreading mechanism was also ruled out in the Igf2r region (19), which showed that the active chromatin is interspersed through modifications localized exclusively on regulatory elements flanking active proteins.…”
Section: Resultsmentioning
confidence: 99%